Sensitivity enhancement of coupled plasmon-waveguide resonance sensors with gold-silver-alumina layers - Alasag, Sumeyye Gulec; Cansever, Nurhan; Aslan, Mustafa M. (SPIE-INT SOC OPTICAL ENGINEERING, 2012)
Coupling surface plasmon resonance mode to waveguide mode(s) by simply forming a dielectric layer on top of the metallic layer can improve the sensor's response to molecular variations. In this study, optimization of Coupled Plasmon - Waveguide Resonance (CPWR) sensors' layers to enhance their sensitivities is investigated. Optimizations of wavelength and thicknesses for highest sensitivities of the angularly interrogated CPWR sensors are accomplished with Fresnel equations and the full width half maximum calculations. Sensitivities are determined for three different film layer configurations that consist of: (I) gold-alumina, (II) silver-alumina, and (III) gold-silver-alumina layers. Optimum thicknesses and wavelength combinations for highest sensitivities are calculated in four steps in the spectral and the physical domains. The sensitivities averaged for the biolayer refractive index varying in the range of 1.330-1.385 are mapped around the optimum point of thickness combination as function of metallic and dielectric layer thicknesses at optimum wavelength. Results from our parametric study show that there is approximately 60-fold improvement in the sensitivity for optimized sensor design by comparing with a typical plasmonic sensor. The highest sensor's sensitivity is obtained at lambda = 600 nm with the gold-silver-alumina layer combination. This study develops a detailed understanding of how both the dimensional and the spectral parameters affect the sensitivity of the CPWR sensors.
Keywords: Surface plasmon; coupled plasmon-waveguide resonance; gold; silver; alumina; angularly interrogated; plasmonic sensor; sensitivity; reflectance; BIOSENSORS; FILM; Engineering; Optics; Physics